"I Don't Owe You, But I Am Committed": Does Felt Obligation Matter on the Effect of Green Training on Employee Environmental Commitment?. (March 2021) - Paillé, Pascal; Valéau, Patrick
This study investigates the contingent effect of felt obligation to care about and aid the organization on the indirect effect of green training on employee environmental commitment through perceived organizational support for the environment. As hypothesized, based on data from 384 employees, our study found that the positive mediating effect is strengthened when felt obligation is low. The implications of these findings are twofold: They indicate that the development of employee environmental commitment is based on employees' perception that their employer supports their environmental initiatives by improving environmental skills. They also suggest that this process has little additional effect of employees already feeling obliged to do whatever they can to help their organization reach its goals, whatever they may but is crucial for employees with low-felt obligation. The article ends with a discussion of the findings in the light of the relevant environmental literature. Limitations and future research are also discussed.